Kryteria fiskalne konwergencji i szanse ich spełnienia przez Polskę - Jastrzębska, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
For the member countries of European Union the most important thing is to balance budget or at least to minimize budget deficit according to the negative influence of rising budget deficit on prices. The European Commission estimates the level of relation between budget deficit and Gross Domestic Product and the relation between gross public debt and Gross Domestic Product. The European Authorities are able to force the member countries to obey the fiscal rules. If not, there are some kinds of punishment. For example for Poland it is loss of grants from European Funds. The European Council says that it is impossible for Poland to meet fiscal criteria in the year 2007 concerning the activity described by Polish government in Convergence Programme. The Council suggests to our government how to decrease budget deficit. And also the government prepares programmes steering on minimizing budget deficit and public debt. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 180-189